POST-TRAUMATIC STRESS DISORDER IN COVID-19 PCR POSITIVE PATIENTS; ITS FREQUENCY AND PSYCHOSOCIAL RISK FACTORS HAVE BEEN OBSERVED IN ENT AND NEUROLOGY OUTPATIENT’S CLINICS - Mahmood, Kausar; Feroz, Shanila; Udaipurwala, Iqbal Hussain; Anwar, Aaqil; Tareen, Owais Khan; Nisa, Zaib Un (Pakistan Armed Forces Medical Journal, 2021)
Objective: To find out the occurrence and psychosocial risk factors of post-traumatic stress disorder in COVID-19 polymerase chain reaction (PCR) positive patients presented to ENT and neurology clinics of a tertiary care hospital. Study Design: Cross-sectional study. Place and Duration of Study: Creek General Hospital, Karachi, Pakistan, from Sep to Dec 2020. Methodology: Total 60 patients with positive COVID-19 PCR test were included. After taking written and informed consent, they were evaluated using a semi-structured questionnaire. Questionnaire comprises of four main parts; first part includes demographic data, second part includes information about the course of COVID-19 in patient and other members of family, third part comprised of reasons of anxiety during COVID-19 and fourth part consist of Impact of Event Scale-revised (IES-R). Data was entered and analyzed through SPSS-23. Results: Out of total 60 patients, 36 (60%) had post COVID stress disorder. Females were affected more than the males (63% vs. 57%), above 50 years of age were affected more than below 50 years of age (81% vs 52%), singles were affected more than married (72% vs 38%) and lower socio-economic status were affected more than higher (65% vs 50%). Conclusion: PTSD was observed as long-term psychiatric problem leading to significant morbidity and mortality in patients with COVID-19 infection.